Reporting drought: framing an anthropogenic natural disaster in the South African mainstream publication, City Press, over three years (2015-2018) - Matyobeni, Thandiwe (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
This study interrogates how the ongoing anthropogenic drought, declared a disaster in five South African provinces in 2015, has been represented by mainstream news media. The news media enables public participation which is vital to climate action and the regulation of harmful neoliberal practices that fuel climate change and are thus necessary to provide information about climate change and to support political interventions. Despite the gravity of the drought crisis, there is a severe lack of public opinion about it and the complex weather patterns to which it is attributed. This study thus investigates how the drought has been framed by mainstream news media in South Africa, confining itself to a single title, the City Press. To analyse representations of drought in the City Press, this study adopts a Foucauldian approach to discourse which considers representations as meaning constructed through language. The knowledge perpetuated in news texts is thus frequently perceived as the 'truth' about the drought. This knowledge is imbued with power as those in positions of authority determine what is articulated as truth. Through various institutional practices, journalists limit what is said about the drought, framing it in particular ways and privileging particular voices. What the public learns about the drought (and in turn, climate change) is thus limited by the norms and routines of the journalistic regime and the corporate nature of ownership. Notably, the City Press operates within the neoliberal economic order to which climate change is attributed. This study is located within the Cultural Studies and Journalism Studies paradigms and is further informed by a qualitative methodology and two methods of textual analysis, that is, thematic analysis and Critical Discourse Analysis. The sampling process produced a database of 26 news texts published by the City Press between the years 2015 to 2018. Five texts were purposively selected for an in-depth analysis based on a broad thematic analysis as reasonably representative of the discourses that recur. Although the City Press positions itself as a critical purveyor of political information, only three themes recur in the texts. These themes position drought in relation to the agricultural economy and urban infrastructure; foreground the voices of corporate entities; while the climate science behind weather patterns is inadequately interpreted. Any discussion of climate change and alternatives to mainstream economic practices is almost entirely omitted.
Keywords: City Press; City Press -- Criticism, Textual; Droughts -- South Africa; Mass media and the environment -- South Africa; Climatic changes in mass media -- South Africa; Press -- South Africa